Search for zoonotic camel infections posing a potential human health threat in Kazakhstan - Karamendin К.О.; Kydyrmanov, A.I.; Khan, E.Ya.; Seidalina, A.B.; Kasymbekov Е.Т. (Fundamental and Experimental Biology, 2022)
Worldwide studies have shown the importance of controlling the spread of zoonotic infections. In recent years, new pandemic strains of coronaviruses in camels have been identified, which necessitates regular monitoring of the state of viral populations of this animal. The research scope is toidentify the spectrum of viral and bacterial populations circulating in camels in Kazakhstan posing threat to human and animal health, their mo-lecular genetic studies. Virological and molecular-genetic methods were used: taking biological samples from camels, extracting nucleic acids from them, obtaining libraries for massive parallel sequencing, bioinformatic analysis of the data obtained and serological tests. Massive parallel sequencingrevealed the viral contigs clas-sified into 3 large genera: Pestivirus, Circovirus, and Hepevirus. Of particular interest is the discovery of short sequences similar to those of the hepatitis E virus, which requires further deeper studies in this direction. Sero-logical studies of camels from the Mangystau region did not reveal antibodies to the Middle East respiratory syndrome virus (MERS-CoV), which shows their absence in active circulation or much time has been passed since their possible presence in camels. The study of viral metagenomes of camels in the region close to the Middle East is an important task of scientific research. A metagenomic study will allow to detect not only coronaviruses, but also to analyze other and unknown viral infections that are important both for agriculture and for the health of the human population.